2019
DOI: 10.1093/rheumatology/kez040
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fluorodeoxyglucose uptake assessed by positron emission tomography–computed tomography as a biomarker of inflammatory myopathies disease activity

Abstract: Objective To devise a simple PET-CT score for measurement of muscle disease activity in patients with inflammatory myopathies (IMs) and to assess its validity. Methods A total of 44 PET-CT examinations in 34 IM patients (performed during cancer screening) and 20 PET-CT examinations in matched controls (investigated for pulmonary nodules with a conclusion of benignity) were analysed. Maximal standardized uptake values (SUVmax)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…FDG PET imaging also permits to detect muscle inflammation, but normal values for muscle Standardized Uptake Value (SUV) are difficult to define (120)(121)(122)(123). The sensitivity for muscle inflammation is broad: 33-90% (120)(121)(122)124) in IIM depending on muscle inflammation definition (qualitative or quantitative definition). Muscle SUV seems correlated to CK levels and MMT (124,125), and one study found a correlation between inflammation on biopsies and SUV (124).…”
Section: [18f] Fluorodeoxyglucose Positron Emission Tomography/computed Tomography (Fdg Pet)mentioning
confidence: 99%
See 1 more Smart Citation
“…FDG PET imaging also permits to detect muscle inflammation, but normal values for muscle Standardized Uptake Value (SUV) are difficult to define (120)(121)(122)(123). The sensitivity for muscle inflammation is broad: 33-90% (120)(121)(122)124) in IIM depending on muscle inflammation definition (qualitative or quantitative definition). Muscle SUV seems correlated to CK levels and MMT (124,125), and one study found a correlation between inflammation on biopsies and SUV (124).…”
Section: [18f] Fluorodeoxyglucose Positron Emission Tomography/computed Tomography (Fdg Pet)mentioning
confidence: 99%
“…When compared to a validated technique for assessment of IIM activity, FDG‐PET showed that muscle FDG uptake measurement has high sensitivity and specificity to distinguish active from non‐active muscle disease and a good sensitivity to detect changes in muscle disease activity (122).…”
Section: Muscle Imaging Developmentmentioning
confidence: 99%
“…Previously reported results were similarly ambiguous. Some authors found a correlation between SUV of FDG and myositis severity, muscle strength, and the extent of inflammatory infiltrate in biopsy [25][26][27][28], while others found no correlation of FDG findings with paraclinical or clinical parameters [13,29,30]. The reason may be a heterogeneous disease manifestation as described by Sun et al, who noted that an average SUV is not necessarily representative of the activity and severity of muscles specifically affected in IIM patients [31].…”
Section: Discussionmentioning
confidence: 98%
“…Antisynthetase Syndrome is a rare and poorly defined autoimmune disease associated with interstitial lung disease, polymyositis, and dermatomyositis 1 2 3 4 5 6 . MRI can help differentiating fatty muscle lesions from inflammatory changes; however, the ability to perform a whole-body examination is restricted.…”
Section: Discussionmentioning
confidence: 99%